Choice and Duration of Antimicrobial Therapy for Neonatal Sepsis and Meningitis - Sindhu Sivanandan; Amuchou S. Soraisham; Kamala Swarnam (Hindawi Limited, 2011)
Neonatal sepsis is associated with increased mortality and morbidity including neurodevelopmental impairment and prolonged hospital stay. Signs and symptoms of sepsis are nonspecific, and empiric antimicrobial therapy is promptly initiated after obtaining appropriate cultures. However, many preterm and low birth weight infants who do not have infection receive antimicrobial agents during hospital stay. Prolonged and unnecessary use of antimicrobial agents is associated with deleterious effects on the host and the environment. Traditionally, the choice of antimicrobial agents is based on the local policy, and the duration of therapy is decided by the treating physician based on clinical symptoms and blood culture results. In this paper, we discuss briefly the causative organism of neonatal sepsis in both the developed and developing countries. We review the evidence for appropriate choice of empiric antimicrobial agents and optimal duration of therapy in neonates with suspected sepsis, culture-proven sepsis, and meningitis. Moreover, there is significant similarity between the causative organisms for early- and late-onset sepsis in developing countries. The choice of antibiotic described in this paper may be more applicable in developed countries.